Invasion of Diabetic and Atherosclerotic Vessels Patients with Periopathogen Spirochete Treponema denticola in Iraqi Population - AL-Nasrawi; Adil Ateyah Abd Ali; Ali Kadhim Aljarah; Hayder Ali Muhammed (Indian Journal of Forensic Medicine & Toxicology, 2021)
Both Periodontitis & Atherosclerosis of Cardiovascular system are chronic inflammatory disorders can beperformed by invasion of their connective tissues with aerobic & anaerobic infectious bacteria & formationof polymicrobial biofilms. Microbial & metabolic plaques are considered to be the initiating factor for manyinfectious & metabolic diseases, invasion of an oral & systemic organs with various opportunistic pathogenshave been reported in many populations. Several studies have been published Conventional & Real timePCR with 16S r RNA gene to improve the existence of the DNA molecules of the most invasive periodonticspathogens in atheromatous plaques of diabetic & cardiovascular blood vessels disease patients.In the present study, among 100 atherosclerotic & diabetic patients suffered from various degrees of ischemicheart disease, the DNA molecules of Treponema denticola was detected in (45/100)45% of atheromatousplaque samples significantly in male 28 /45 (62%) more than 17/45(38%) in female patients (p = 0.07) withno significant importance in cardiovascular & diabetic patients more than 50 years old 23/45(51%) whichwas approximate to 22/45(49%) in younger than 50 years old. As well as, T. denticola DNA molecules weresignificantly displayed in atheromatous plaques of type (1, 2) diabetic patients 35 /45 (78%) more than innon-diabetic group 10/45(22%) (p= 0.07) & T. denticola DNA molecules did not displayed in the controllergroup.In conclusion: the present cross sectional study demonstrated the invasion of atheromatous plaques ofcardiovascular atherosclerotic vessels & diabetic patients with highly aggressive anaerobic periodontalspirochetes T. denticola, these results improve the existence of additional risk factor that interfere withthe pathogenesis of periodontitis & genesis of cardiovascular atherosclerosis & may be correlated with theatherosclerosis & diabetes mellitus diseases patients in Iraqi population.